1988
DOI: 10.1063/1.99942
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation of impurities in GaAs amorphized by ion implantation

Abstract: Impurities in a GaAs layer that had been amorphized by ion implantation were observed to precipitate upon annealing. Photoluminescence spectra indicated that the resulting high electrical resistivity could be attributed to the formation of neutral impurity complexes rather than a compensation mechanism. Impurities studied were implanted Si and Se. Transmission electron microscopy and x-ray microanalysis were used to identify impurity precipitates and related stacking fault tetrahedra. These results correlate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…High resolution electron microscopy studies suggested that they were stacking fault tetrahedra. Such defects have been previously reported in implanted GaAs [17,18]. The main structural feature visible in this sample was a band of defects present in a layer at a depths from ~0.2 µm to ~0.3 µm below the surface.…”
mentioning
confidence: 65%
“…High resolution electron microscopy studies suggested that they were stacking fault tetrahedra. Such defects have been previously reported in implanted GaAs [17,18]. The main structural feature visible in this sample was a band of defects present in a layer at a depths from ~0.2 µm to ~0.3 µm below the surface.…”
mentioning
confidence: 65%
“…The most common n-type amphoteric dopant used in InGaAs, GaAs and InP is Si. Silicon has been extensively studied in InGaAs, GaAs, and InP (9,11,12,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Silicon remains the most attractive n-type dopants in InGaAs due to its limited diffusivity and post implant activation values of 0.9-1×10 19 /cm 3 .…”
Section: Amphoteric Impuritiesmentioning
confidence: 99%
“…Silicon remains the most attractive n-type dopants in InGaAs due to its limited diffusivity and post implant activation values of 0.9-1×10 19 /cm 3 . Generally the activation of Si improves with increasing annealing temperature however Si has been shown to change types in GaAs where it goes from n to p type at annealing temperatures above 1050°C (24). Ge has seen some limited use in III-V's as a dopant but dose and anneal dependent type changes have been seen in GaAs and it generally exhibits lower activation values compared to Si implants (35).…”
Section: Amphoteric Impuritiesmentioning
confidence: 99%
“…Such defects have been previously reported in implanted GaAs. [16][17] In the S and N co-implanted sample there are pits observed at the surface formed possibly as a results of too high an annealing temperature or stacking fault formation. In this sample instead of a band of stacking fault tetrahedra a broad layer containing a high density of small voids (of an average size of about 4-5 nm) was observed (Fig.3f), similar to those shown in Fig.…”
Section: -15mentioning
confidence: 99%